2021
DOI: 10.4178/epih.e2021052
|View full text |Cite
|
Sign up to set email alerts
|

Data resource profile: the Korea National Hospital Discharge In-depth Injury Survey

Abstract: The Korea National Hospital Discharge In-depth Injury Survey (KNHDIS), which was started in 2005, is a national probability survey of general hospitals in Korea with 100 or more beds conducted by the Korea Disease Control and Prevention Agency (KDCA). The KNHDIS captures approximately 9% of discharged cases from sampled hospitals using a 2-stage stratified cluster sampling scheme, among which 13% are injury related cases, defined as S00-T98 (injury, poisoning, and certain other consequences of external causes)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
0
16
2
Order By: Relevance
“…In this study, those who reported poor SROH had a lower slope of decline than those in the good SROH group, despite all groups showing a significantly decreasing trend for both men and women. The declining trend in fall experiences among all groups could be explained by the efforts of health authorities in Korea to develop and implement evidence-based guidelines for fall prevention,12 provide fall prevention interventions34 and conduct National Injury Surveillance and Prevention to minimise damage and social losses resulting from injury and falls 35…”
Section: Discussionmentioning
confidence: 99%
“…In this study, those who reported poor SROH had a lower slope of decline than those in the good SROH group, despite all groups showing a significantly decreasing trend for both men and women. The declining trend in fall experiences among all groups could be explained by the efforts of health authorities in Korea to develop and implement evidence-based guidelines for fall prevention,12 provide fall prevention interventions34 and conduct National Injury Surveillance and Prevention to minimise damage and social losses resulting from injury and falls 35…”
Section: Discussionmentioning
confidence: 99%
“…A stratified two-stage cluster sampling method was used, with individual hospitals as the primary sampling unit and discharged patients in a sampled hospital as the secondary sampling unit. 18 The study hospitals were selected based on a cluster random sample of hospitals stratified by geographic location and number of beds. To reflect the complex sampling, weightage was assigned to the variable that was the variance of the estimated total number of discharged patients, the medical institution code corresponding to the primary sampling unit of the sample design was set to cluster, and the number of beds was set to strata.…”
Section: Methodsmentioning
confidence: 99%
“…This study utilized secondary data from the Korea National Hospital Discharge In-depth Injury Survey conducted between 2006 and 2020. The survey, conducted annually by the Korea Disease Control and Prevention Agency(KDCA) since 2005, aims to inform the development of cost-effective health policies by capturing the scale and characteristics of discharged patients (14).…”
Section: Study Populationmentioning
confidence: 99%
“…The survey targets patients discharged from general hospitals with 100 beds or more nationwide. Based on the hospital size, 170 hospitals are selected as sample hospitals, collecting demographic information, admission details, disease, and treatment information, as well as injury data of discharged patients from medical records (14).…”
Section: Study Populationmentioning
confidence: 99%